A revised catalog of the mite family Phytoseiidae - de Moraes, G. J.; Mcmurtry, J. A.; Denmark, H. A.; Campos, C. B. (Zootaxa, 2004)
Mites of the family Phytoseiidae are the most common predators of phytophagous mites on most plant species. Some species are widely studied and used for the biological control of mite pests. Many new species continue to be discovered as collections are intensified in certain regions or habitats, e.g. in Africa, Asia, Central and South America. The last catalog of Moraes et al. (1986) included about 1500 described species. This updated catalog includes almost 2250 species. As in the last catalog, it includes references to descriptions and redescriptions of species, synonymies and recorded world distributions.